HUBUNGAN ANTARA KECERDASAN EMOSIONAL (EQ) DAN MOTIVASI BELAJAR DENGAN PERILAKU BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMPN 01 JENANGAN PONOROGO - Wahyuningttyas, Putri (IAIN Ponorogo, 2014)
Abstract: Abstract; several things need to get attention from student are emotional quotation (EQ), learn motivation and study behavioral. Various research proved that many people who have high IQ often fall because unable to monitor its emotion better. As well as learn motivation, impossible student to do learning activity if they had no motivation to learn. With EQ and high learn motivation, hence student expected to have good learn behavior so the result of learning filled. Relate to that, target of this research is to know how emotional question (EQ), learn motivation and grade 7th student study behavioral at Islamic study and to know how relation between emotional question (EQ) and learn motivation and grade 7th student study behavioral at Islamic study in SMPN 1 Jenangan, Ponorogo. This study represent quantitative research which is population grade 7th student, 169 students. Sample technique used sampling random simple with 117 students. This research use questioner, observation, and documentation as collecting data. While its data analysis use double correlation formula. Result of this research found that there are 64,10 % respondent with enough EQ; 61,54 % respondent with enough learn motivation; there are 64,10 % respondent with enough study behavioral; there are significant correlation between emotional question (EQ) and learn motivation with grade 7th student study behavioral at Islamic study ( PAI) in SMPN 01 Jenangan, Ponorogo with coefficient correlation equal to 0,823.Â Ù ÙØ®Øµ:ÙÙØ§Ù Ø£Ù ÙØ± ÙØ§Ø¨Ø¯ Ù Ù Ø§ÙØ§ÙØªÙ Ø§Ù Ø¨ÙØ§ Ù Ù ÙØ¨Ù Ø§ÙØ·Ø§ÙØ¨ ØÙÙ ÙØ¯Ø±Ø³ ÙÙÙ Ø§ÙØ°ÙØ§Ø¡ Ø§ÙØ¹Ø§Ø·ÙÙ ÙØ¯Ø§ÙØ¹ Ø§ÙØªØ¹ÙÙ ÙØ³ÙÙÙ Ø§ÙØªØ¹ÙÙ ÙØ¯ÙÙ. ÙÙØ¯ Ø£Ø«Ø¨ØªØª Ø§ÙØ¯Ø±Ø§Ø³Ø§Øª Ø£Ù ÙÙØ§Ù Ø£Ø°ÙÙØ§Ø¡ ÙÙÙÙÙ ÙØ´ÙÙØ§ ÙØ¹Ø¯Ù ÙØ¯Ø±ØªÙÙ Ø¹ÙÙ ØªÙØ³ÙÙ Ø¹ÙØ§Ø·ÙÙÙ Ø¬ÙØ¯Ø§. ÙÙÙØ°Ø§ Ù Ø§ ÙØªØ¹ÙÙ Ø¨Ø¯ÙØ§ÙØ¹ Ø§ÙØªØ¹ÙÙ . ÙØ§ ÙÙ ÙÙ Ø£Ù ÙØ¯Ø±Ø³ Ø§ÙØ·Ø§ÙØ¨ Ø¯ÙÙ Ø£Ù ÙÙÙÙ ÙÙ Ø¯ÙØ§ÙØ¹ ÙÙØªØ¹ÙÙ ÙÙ ÙÙØ³Ù. ÙØ¨Ø§ÙØ°ÙØ§Ø¡ Ø§ÙØ¹Ø§Ø·ÙÙ ÙØ¯Ø§ÙØ¹ Ø§ÙØªØ¹ÙÙ Ø§ÙØ¹Ø§ÙÙØ© ÙØ³ØªØ·ÙØ¹ Ø§ÙØ·Ø§ÙØ¨ Ø£Ù ÙÙØ¬Ø¯ ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØªØ¹ÙÙ Ù Ø§ÙØ¬ÙØ¯ ØØªÙ ÙØØµÙ Ø¹ÙÙ ÙØªØ§Ø¦Ø¬ Ø§ÙØªØ¹ÙÙ Ø§ÙØ¬ÙØ¯Ø©. ÙØ¨ÙØ°Ø§ ØªÙÙÙ Ø£ÙØ¯Ø§Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ù Ø¹Ø±ÙØ© Ø§ÙØ°ÙØ§Ø¡ Ø§ÙØ¹Ø§Ø·ÙÙ ÙØ¯Ø§ÙØ¹ ØªØ¹ÙÙ Ø·ÙØ§Ø¨ Ø§ÙØµÙ Ø§ÙØ³Ø§Ø¨Ø¹ ÙØ³ÙÙÙÙÙ ÙÙÙ ÙÙÙ Ø¹Ø±ÙØ© Ø§ÙØ§Ø±ØªØ¨Ø§Ø· Ø¨ÙÙ Ø§ÙØ°ÙØ§Ø¡ Ø§ÙØ¹Ø§Ø·ÙÙ ÙØ¨ÙÙ Ø¯ÙØ§ÙØ¹ ØªØ¹ÙÙ Ø·ÙØ§Ø¨ Ø§ÙØµÙ Ø§ÙØ³Ø§Ø¨Ø¹ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«Ø§ÙÙÙØ© Ø§ÙØ¹Ø§Ù Ø© Ø§ÙØÙÙÙ ÙØ©Â Ø§ÙØ£ÙÙÙ Ø¬ÙØ§Ø¹Ø§Ù ÙÙÙÙØ±ÙØºÙ ÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©Â . ÙÙÙØ¹ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¨ØØ« ÙÙ ÙÙØ ÙÙ Ø¬ØªÙ Ø¹ ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ø·ÙØ§Ø¨ Ø§ÙØµÙ Ø§ÙØ³Ø§Ø¨Ø¹ ÙØ¹Ø¯Ø¯ÙÙ 169 Ø·Ø§ÙØ¨Ø§Ø ÙØªØ¬Ù Ø¹ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø¨Ø§ÙØ§Ø³ØªØ¨ÙØ§ÙØ§Øª ÙØ§ÙÙ ÙØ§ØØ¸Ø© ÙØ§ÙÙØ«Ø§Ø¦Ù Ø§ÙÙ ÙØªÙØ¨Ø©. Ø£Ù Ø§ ØªØÙÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª ÙØ¨ØªØÙÙÙ Ø§ÙØ§Ø±ØªØ¨Ø§Ø· Ø§ÙØªØ¹Ø¯Ø¯Ù. ÙÙØªØ§Ø¦Ø¬ ÙØ°Ø§ Ø§ÙØ¨ØØ«Ø ÙÙØ§Ù 64,10% Ù Ù Ø§ÙÙ Ø³ØªØ¬ÙØ¨ÙÙ ÙÙÙ Ø§ÙØ°ÙØ§Ø¡ Ø§ÙØ¹Ø§Ø·ÙÙ Ø§ÙÙØ§ÙÙØ Ù % 61,54 Ù Ù Ø§ÙÙ Ø³ØªØ¬ÙØ¨ÙÙ ÙÙÙ Ø¯ÙØ§ÙØ¹ Ø§ÙØªØ¹ÙÙ Ø§ÙÙØ§ÙÙØ©Ø Ù % 64,10 Ù Ù Ø§ÙÙ Ø³ØªØ¬ÙØ¨ÙÙ ÙÙÙ Ø³ÙÙÙ Ø§ÙØªØ¹ÙÙ Ø§ÙØ¬ÙØ¯Ø ÙÙÙØ§Ù Ø§Ø±ØªØ¨Ø§Ø· Ø°Ù Ù Ø¹ÙÙ Ø¨ÙÙ Ø§ÙØ°ÙØ§Ø¡ Ø§ÙØ¹Ø§Ø·ÙÙ ÙØ¯ÙØ§ÙØ¹ Ø§ÙØªØ¹ÙÙ ÙØ¨ÙÙ Ø³ÙÙÙ Ø§ÙØªØ¹ÙÙ ÙØ¯Ù Ø·ÙØ§Ø¨ Ø§ÙØµÙ Ø§ÙØ³Ø§Ø¨Ø¹ ÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ«Ø§ÙÙÙØ© Ø§ÙØ¹Ø§Ù Ø© Ø§ÙØÙÙÙ ÙØ©Â (1) Ø¬ÙØ§Ø¹Ø§Ù ÙÙÙÙØ±ÙØºÙ ÙØ¹Ø¯Ø¯Ù 0,823.Â Keywords: Kecerdasan Emosional (EQ), motivasi belajar, perilaku belajar